Coexistence of blaNDM-1, blaOXA-51, blaOXA-23, and armA in conjunction with novel mutations detected in RND efflux pump regulators in tigecycline resistant clinical isolates of Acinetobacter baumannii. Issue 1 (15th June 2022) - Sawant, Ajit Ramesh; Pagal, Sudhakar; Amar, Ashutosh Kumar; Panda, Lipsa; devi C, Sheela; Shashikala, P; Kanungo, Reba; Prashanth, K
Abstract: This study has investigated a total of 51 Acinetobacter baumannii isolates for the prevalence of resistant determinants in tigecycline susceptible and non-susceptible clinical isolates of A. baumannii . Antimicrobial susceptibility testing revealed 74% of isolates were tigecycline resistant. Mutations in RND-efflux pump regulatory genes and the expression of efflux pump genes were measured in tigecycline resistant isolates. There was a strong co-relation between the bla NDM-1 and armA wherein majority of the isolates that are positive for bla NDM-1 have also harbored armA . Compared with TSAB (tigecycline susceptible A. baumannii ), TNAB (tigecycline non-susceptible A. baumannii ) isolates show increased distribution of bla NDM-1 ( P = 0.048), bla IMP-1 ( P < 0.0001) and bla OXA-51 ( P = 0.0029) carbapenemase genes. The variants of RND-efflux pump regulatory genes due to amino-acid mutations in adeS (F12S, K84E, W61R, N268H and Q299R) and adeL (G21R and Q262R) were identified in tigecycline resistant isolates as well as ISAba1 mediated disruption of adeN were observed causing overexpression of adeIJK efflux pump. Additionally, mutations in adeRS were also associated with increased expression of adeABC efflux pump. Besides, TNAB isolates showed significantly ( P < 0.0001) higher ability of biofilm formation as compared to TSAB isolates. The tigecycline resistance due to mutations in contemporary A. baumannii isolates having a higher ability to form biofilm may pose therapeutic difficulties. Abstract : Novel mutations (deletions/substitutions) detected in efflux pump regulatory genes were associated with increased levels of tigecycline resistance.